211k views
2 votes
Find the sum of the series and show your process for finding each term leading to the final sum.

∑5k=3(−2k+5)

1 Answer

7 votes

Answer:


\large\boxed{\sum\limits_(k=3)^5(-2k+5)=-9}

Explanation:


\sum\limits_(k=3)^5(-2k+5)\to a_k=-2k+5\\\\\text{Put}\ k=3,\ k=4\ \text{and}\ k=5:\\\\a_3=-2(3)+5=-6+5=-1\\a_4=-2(4)+5=-8+5=-3\\a_5=-2(5)+5=-10+5=-5\\\\\sum\limits_(k=3)^5(-2k+5)=-1+(-3)+(-5)=-9

User Salomon
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.